Seamless Integration of an Elastomer with Electrode Matrix and its In‐Situ Conversion into a Solid State Electrolyte for Robust Li‐Ion Batteries. (26th June 2013) - Ombaba, Matthew M.; Vidu, Ruxandra; Jayaraman, Logeeswaran Veerayah; Triplett, Mark; Hsu, Jonathan; Islam, M. Saif
Abstract A unique way of robustly integrating an elastomer film onto a graphitic anode and then post process it into a solid‐state electrolyte for lithium‐ion battery applications is reported. The mutual solvability of the elastomer and the binder of the graphitic anode (carboxymethyl cellulose, (CMC)) in dimethylformamide facilitates the fusion of the two heterogeneous layers. Dimensional dynamics evolved during the integrated elastomer conversion into a solid electrolyte by liquid electrolyte uptake reveal a notable preferential uniaxial elongation along the normal plane. In contrast, the non‐integrated counterpart elongates along the transversal axis. These elastomer exhibits high ionic conductance (≈10–2 S cm−1). Half‐cells constructed with our electrolyte integrated electrode exhibit magnificent reduction and oxidation (REDOX) behavior. The efficient charge transfer across the snugly confined semi‐solid electrolyte/electrode interface layer leads to a high rate capability of 0.31 mAh cm−2 (41 mAh g−1) at 2 C which is double that of a graphitic conventional half‐cell. Unlike regular graphitic electrodes which degrade over time, this electrode remains robust, thanks to its propensity to retain its inherent elasticity. This work demonstrates a facile and scalable paradigm, in fabrication of flexible electrolytes that can easily be integrated to 3D devices and opens opportunities for developing, structurally conformable batteries of varied geometries.